Gas phase imidazole methylation on zeolites and HPA/SiO2: Study of acid site requirements and catalyst deactivation - Vanoy Villamil, Michael Nicolás (2013)
The gas-phase alkylation of imidazole with methanol was studied at 523 K on solid acids such as HPA/SiO2 and zeolites HMCM22, HBEA, NaY, ZnY and HY. The nature, density and strength of acid sites were determined by temperature programmed desorption of NH3 coupled with infrared spectra of adsorbed pyridine. Coke formation was studied by temperature programmed oxidation technique. On all the samples, the selectivity to N-methylimidazole was greater than 98%. Catalysts presenting essentially Lewis (NaY and ZnY) or Brønsted (HPA/SiO2) acidity did not promote efficiently the methylation of imidazole and yielded less than 20% of N-methylimidazole. In contrast, on samples containing similar concentration of Lewis and Brønsted acid sites (HY, HBEA, HMCM22) the N-methylimidazole yield was between 60 % (HMCM22) and 100% (HY). All the samples deactivated during the 4 h catalytic tests and formed significant amounts of coke, between 2.3% (NaY) and 8% (ZnY). Catalytic tests performed at different contact times showed that the initial activity decay diminished with increasing imidazole conversion, suggesting that catalyst deactivation is mainly related with the presence of the reactants, methanol and/or imidazole. In order to gain insight on the catalyst deactivation mechanism, additional catalytic tests using different feed compositions were performed. They showed that the initial catalyst deactivation followed a linear correlation with the partial pressure of imidazole which indicated that the activity decay is essentially related with strong adsorption of imidazole the on surface acid sites.